The value of cardiac magnetic resonance imaging in endocardial fibroelastosis - Wenjiao Xiao; Yuanlin Wang; Weiqin Cheng; Yuting Zhang (Frontiers Media S.A., 2022)
IntroductionEndocardial fibroelastosis (EFE), an uncommon congenital heart disorder often occurring in infants, has a poor prognosis. It is of great significance to perform early diagnosis and accurately analyze cardiac function to enable further clinical treatment and prognosis decisions. This study aimed to explore the findings of cardiac magnetic resonance (CMR) in patients with EFE, including morphological changes and cardiac function analyses. Additionally, we compared the difference in the evaluation of the cardiac function between CMR and echocardiography (Echo).MethodsEleven patients with EFE (nine females and two males, aged between 0.3 and 1.9 years), treated in our hospital, were analyzed retrospectively. Left ventricular posterior wall thickness (LVPW), anterior wall thickness (LVAW), fractional shortening (FS), ejection fraction (EF), end-systolic diameter (ESD), end-diastolic diameter (EDD), end-systolic volume (ESV), and end-diastolic volume (EDV) were assessed using both Echo and CMR. The Original Ross classification and the New York Heart Association functional classification were used to grade the patients' cardiac function. The correlations between clinical cardiac function classification and MRI- and Echo-derived imaging data were determined.ResultsAll patients showed a thickened endocardium and left ventricle globular dilatation on CMR. We observed significant systolic dysfunction and whole or segmental abnormal ventricular movement. Compared with those measured by Echo, the EF, FS, and EDV values were significantly lower when measured using CMR. Compared with Echo measurements, the ESV, ESD, LVAW, and LVPW values were significantly higher when measured using CMR. CMR-measured EF and FS correlated better with the clinical cardiac functional score than those derived from Echo (EF, r = 0.646 > 0.224; FS, r = 0.627 > 0.245, respectively).ConclusionIn patients with EFE, the characteristic morphological changes of the heart could be displayed accurately using CMR. The parameters measured by CMR were more accurate than those of Echo and correlated well with clinical cardiac function scores, mainly because it does not make invalid geometrical assumptions.